Architecture of Conjugated Donor–Acceptor (D–A)‐Type Polymer Films with Cross‐Linked Structures. (5th February 2016) - Huang, Jin; Peng, Bangan; Wang, Weina; Ji, Hanxu; Li, Linling; Xi, Kai; Lai, Wenyong; Zhang, Xinwen; Jia, Xudong
Abstract : A series of new donor–acceptor (D–A)‐type semiconducting conjugated polymers (SCPs), which can form cross‐linked structural and supramolecular assembly films by hydrogen‐bonding, is successfully synthesized. The microstructures of supramolecular assembly films are further investigated by X‐ray diffraction (XRD), high‐ resolution transmission electron microscopy (HRTEM), and variable‐temperature Fourier transform infrared (FT‐IR) absorption spectra. As electronic transmission (ET) materials, the SCPs demonstrate superior properties by means of fabricating electron‐only devices with the configuration of ITO/ET (SCPs)/Ca/Al. According to space‐charge‐limited current (SCLC) measurements, fluorine‐containing SCPs exhibit much smaller threshold voltages and much higher electron mobilities than Alq3 . Meanwhile, a significant enhancement for their luminescence properties is verified by the photoluminescence (PL) and electroluminescent (EL) spectra of cross‐linked‐type SCPs, compared to non‐cross‐linked‐type SCPs. The fabricated polymer light‐emitting diodes (PLEDs) with the configuration of ITO/PEDOT:PSS/EML (SCPs)/BCP/LiF/Al are able to emit the color from green to red with moderately low turn‐on voltages. These results suggested that cross‐linked D–A‐type SCP can become a potential candidate as a kind of multifunctional materials applied in the field of optoelectronic devices. Abstract : A series of new donor–acceptor‐type semiconducting conjugated polymers with hydrogen bonding cross‐linked structure is reported. They are a potential candidate as multifunctional materials applied in the field of optoelectronic devices because of their excellent electronic transmission, photoluminescence, and electroluminescent properties.